Relationships between caregiving stress and sleep quality among family caregivers of older adults with dementia in Thailand - Panawat Sanprakhon; Nujjaree Chaimongkol; Pornpat Hengudomsub (Belitung Nursing Journal, 2022)
Background: Providing care for older people with memory loss is a significantly stressful task. The caregiver experienced deterioration of the care recipients regarding their cognitive and functioning abilities, often resulting in the caregiver’s feelings of distress, stress, and unsatisfactory sleep quality.  Objective: This cross-sectional study aimed to examine the relationships between caregiving stress and sleep quality among family caregivers of older adults with dementia.  Methods: A simple random sampling method was used to recruit participants of seventy-two family caregivers who received care from a community long-term care facility at two primary hospitals in Thailand. Research instruments included the Relative Stress Scale and the Pittsburgh Sleep Quality Index. The data were analyzed using descriptive statistics, means, standard deviation, and simple linear regression. Results: The study revealed that caregivers had a high level of caregiving stress (M = 49.68, SD = 4.71), and poor sleep quality (M = 12.44, SD = 3.60). Caregiving stress was positively correlated with poor sleep quality (r = 0.54, p < 0.01) with a large relationship. Conclusion: Thai family caregivers of people with dementia reported high stress level and had poor sleep quality. The findings suggest that nurses in primary health care should focus on assessing stress levels and sleep quality as well as improving sleep quality for family caregivers by developing interventions.